MITOCHONDRIAL CYTOCHROME B GENE BASED PHYLOGENY OF LOHI AND THALLI SHEEP BREEDS OF PAKISTAN - M. E. Babar a; T. Hussaina; H. Sadia; A. Nadeem; M. Z. Kamran; N. Badshah (Journal of Animal and Plant Sciences, 2014)
Small ruminants (sheep and goat) are major contributors to the livestock sector of Pakistan with 95.7 million heads raised mainly for meat, milk and wool. The 34 sheep breeds spread throughout the country manifest precious genetic diversity in Pakistan. The genetic structure of two sheep breeds (Lohi and Thalli) was explored using complete mitochondrial Cytochrome b gene sequences (1140 bp). The sequence analysis revealed four Lohi and five Thalli haplotypes. There were more transitions than transversions in these sequences. The phylogenetic analysis of Lohi and Thalli breeds with previously reported sheep breeds from different countries indicated two distinct groups. Pakistani and Indian sheep breeds clustered together while Turkish breeds clustered with European sheep breeds. This study was found informative for establishing relationships between breeds from different parts of the world. This study may facilitate the future researchers and breeders for better understanding the genetic interactions and breed differentiation for devising future breeding and conservation strategies to preserve the rich animal genetic reservoir of the country.
Keywords: Sheep genetic diversity; Mitochondrial Cytochrome b gene; Haplotypes; Phylogenetic analysis; Pakistan